JALUR INFEKSI Beauveria bassiana DAN Metarhizium anisopliae SEBAGAI PENGENDALI HAYATI COLEOPTERA:Oryctes rhinoceros L. - Dyah Nuning Erawati; Irma Wardati; Suharto Suharto; Joni Murti Mulyo Aji; Novita Cholifah Ida; Yeni Suprapti (Politeknik Negeri Lampung., 2021)
Recent co-evolutionary studies of insect-pathogens have shown that entomopathogenic fungi have a greater potential for oral toxicity in terms of virulence in the mouth infection of insect pests. Therefore, it is necessary to conduct research on finding the route of infection of B. bassiana and M. anisopliae through the mouth in the larvae of the rhinoceros beetle O. rhinoceros. The purpose of this study was to analyze the path of infection of B. bassiana and M. anisopliae in O. rhinoceros larvae through exposure to the entompotagen fungus. The study was conducted at the Plant Protection Laboratory Politeknik Negeri Jember using a single factor Completely Randomized Design (CRD) with B. bassiana and M. anisopliae isolates from Temanggung, Jember and Jombang. Data analysis used Analysis of Variance and further analysis used Least Significant Difference Test at 5% level. The results showed that all isolates were able to infect and cause mortality in the test insects. MJb isolate had the highest effectiveness with the mortality rate of the test insects reaching 100% and the highest spore density with an average of 8.9 x 109 conidia/ml on day 6 after application. The hyphae that were abundant in the abdomen of cadaveric infected with M. anisopliae were different from the hyphae which grew more on the head of insects infected with B. bassiana, confirming previous research on the route of B. bassiana infection through oral toxicity. These results will be useful in providing new information regarding potential pathways of infection of B. bassiana in O. rhinoceros larvae through oral toxicity mechanisms, which until now have been very little reported. Keywords: entomopathogenic fungi, oral infection, larvae, coleoptera